METODE PENAFSIRAN AL-ZUHAYLî DALAM AL-TAFSîR AL-MUNîR - Ainol, Ainol (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2011)
The first and the foremost authority interprets the Koran is the Prophet Muhammad because he was receiving a direct Koran. After the Prophet, the authority was followed by his companions, tâbi?în, and mufassir afterward. Interpretations performed above the companions known as tafsîr bi al-ma?thur. This commentary underlies the discussion and its source in history. This method became known as a method of interpretation of the Koran is called the method of history. In addition, the method used at that time was the tafsîr bi al-ra?y underlying source on reasoning and ijtihâd. One contemporary commentator who try to combine the two sources of the interpretation is Wahbah al-Zuhaylî. The interpretation of the content approached the Koran, from a classic interpretation that many make al-ma?thur as the source and from the angle of the many modern and contemporary make ra?y as the source